Association between interleukin 8‐receptor gene (CXCR1 and CXCR2) polymorphisms and urinary tract infection: Evidence from 4097 subjects - Han, Shi‐Sheng; Lu, Yan; Chen, Min; Xu, Yan‐Qiu; Wang, Yi (Nephrology (Carlton, Vic.), 2019)
ABSTRACT Aim The aim of this study was to determine whether a correlation exists between interleukin‐8 receptor polymorphisms and urinary tract infection (UTI) susceptibility. Methods We systematically searched electronic databases including PubMed, Embase, China National Knowledge Infrastructure, and Web of Science up to 5 November 2017 to select appropriate studies that focused on C‐X‐C chemokine receptor type 1 and/or 2 (CXCR1, CXCR2) polymorphisms with susceptibility to UTI. Eight case‐control studies including 2085 patients with UTI and 2012 controls were enrolled in this study. Seven studies of CXCR1 rs2234671 and two studies of rs3138086 were included in the meta‐analyses. Pooled odds ratio (OR) and corresponding 95% confidence interval (CI) were synthesized using fixed‐effects or random‐effects model according to heterogeneity. Results No significant correlations were found between CXCR1 rs2234671 and rs3138086 polymorphisms and UTI susceptibility. However, subgroup analysis showed that rs2234671 was associated with an increased risk of UTI under allelic comparisons (C vs. G, OR = 1.95, 95% CI = 1.07–3.55), heterozygous model (GC vs. GG, OR = 1.93, 95% CI = 1.06–3.50), and dominant model (GC + CC vs. GG, OR = 1.98, 95% CI = 1.07–3.69) in children, especially in paediatric patients with acute pyelonephritis (allelic, OR = 2.43, 95% CI = 1.28–4.60; heterozygous, OR = 2.40, 95% CI = 1.24–4.62; dominant, OR = 2.48, 95% CI = 1.26–4.88). Furthermore, these results remained the same after eliminating paediatric patients with vesicoureteral reflux. Conclusion CXCR1 rs2234671 polymorphism might be associated with an increased risk of UTI in children. Summary at a Glance This meta‐analysis of several case‐control studies showed that polymorphism rs2234671 in the CXCR1 gene may be associated with an increased risk of UTI in Caucasian children, while rs1126579 in the CXCR2 gene may have a protective role in UTI development.